The Influence of Corporate Social Responsibility Disclocure on Accounting Conservatism with State Ownership as a Moderator - Hardana, Richio Putra; Cahyadi, Rino Tam; Wijayanti, Dian (Wahana Riset Akuntansi, 2025)
Purpose – This study aims to examine the effect of corporate social responsibility disclosure on accounting conservatism and the effect of state ownership in moderating the relationship between corporate social responsibility disclosure and accounting conservatism.Design/methodology/approach – This study uses state-owned enterprises and regional-owned enterprises listed on the Indonesia Stock Exchange for the period 2018-2022 as the sample. This research used moderate regression analysis to conduct data analysis.Findings – The results show that corporate social responsibility disclosure has a positive effect on accounting conservatism. These results are in line with stakeholder theory which states that companies must pay attention to the interests of all interested parties, not just shareholders. Results also show that state ownership weakens the relationship between corporate social responsibility disclosure and accounting conservatism.Originality/value – This study seeks to fill the gap from previous research on the effect of corporate social responsibility on accounting conservatism since prior research reported inconsistent findings. Due to the lack of evidences in regards to the role of state ownership, this study incorporates state ownership as the moderating variable. The sample was selected based on the Regulation of the Minister of State-Owned Enterprises PER-05/MBU/04/2021 concerning Social and Environmental Responsibility Programs for State-Owned Enterprises.Research limitations/implications – This study has a limitation in the subjectivity of the measurement of CSR. This subjectivity arises when companies do not publish sustainability reports and categorize CSR activities in tables according to the GRI index, and only report CSR activities in the annual report without including a table that aligns the activities with the GRI index. This study has implications in decision making for policy makers in relation to social and environmental responsibility resulting from business activities. Companies are also required to be more transparent in disclosing company performance in maintaining stakeholder trust.